The impact of horizontal violence among nurses on their job burnout: a moderated mediation model - Liu, XuYan; Liang, RenLong; Li, YiWei; Yuan, Yin; Ruan, Tingting; Jian, Rui (Frontiers in Public Health, 2025)
ObjectiveChinese nurses have a heavy workload, and the problem of inter nurse horizontal violence is prominent. Nurses who are subjected to horizontal violence are more likely to experience professional burnout. The aim of this study is to explore the intrinsic relationship between inter nurse horizontal violence and nurse burnout, and to examine the mediating role of psychological detachment in this relationship. In addition, this study also evaluated whether professional mission has a moderating effect in this mediating model.MethodsFrom November to December 2024, this study employed a cross-sectional survey method to recruit nurses from five tertiary first-class public hospitals in the southwest region of Sichuan Province. Surveys were conducted using general information questionnaires, lateral violence among nurses questionnaires, job burnout scales, psychological detachment scales, and professional mission scales. Data obtained from the survey were analyzed using SPSS 27.0 and its macro program Process v4.2.ResultsResearch indicates that inter-nurse horizontal violence is a significant predictor of job burnout, with a positive correlation between the two. Psychological detachment has been identified as playing a partial mediating role in the association between inter-nurse horizontal violence and job burnout, with the mediating effect accounting for 44.73% of the total effect. Furthermore, a sense of professional mission weakens the negative prediction of horizontal violence on psychological detachment and the positive prediction of horizontal violence on job burnout, and moderates the first half of the mediating effect model as well as the direct effect.ConclusionNurses’ psychological detachment ability plays a partial mediating role in horizontal violence and job burnout, with a sense of professional mission moderating this mediation model. Nurses with a strong sense of professional mission are more likely to overcome the distress caused by horizontal violence, enabling them to have a higher degree of psychological detachment, recover during rest, and thus reduce job burnout. Conversely, nurses with a weak sense of professional mission are more prone to experiencing job burnout when subjected to horizontal violence. Therefore, enhancing nurses’ sense of professional mission and psychological detachment ability is beneficial for alleviating job burnout among nurses.